Associations of physical, chemical with thermal changes during coking as coal heats – Experiments on coal maceral concentrates. (1st May 2015) - Xie, W.; Stanger, R.; Wall, T.F.; Lucas, J.A.; Mahoney, M.R.
Highlights: Physical, chemical and thermal events of heating coal macerals were synchronized. Thermo-expansion of coal used up to 21% of the volatiles to drive bubble growth. Vitrinite content affected the swelling temperature region and gas diffusion. Onset of tar evolution was identified as the lowest temperature event as coking. Condensable tars from high vitrinite have a higher overall H/C ratio. Abstract: Dynamic measurements of physical, chemical and thermal changes in the transformation of coal maceral concentrates were made during heating at a rate of 10 °C/min to 1000 °C. The endothermic and exothermic processes were identified by measurements of apparent specific heat while the fluidity was indicated by the estimated thermal conductivity. Measurements of swelling and bed permeability were made, with continuous quantitative elemental analysis of gases and tars as they evolved. Data for two coal concentrates of high and moderate vitrinite indicate that the same reactions and events are occurring for the two samples, but to a greater extent for the high vitrinite sample. The research has noted the significance of evolved tars in the early events, being the lowest temperature event identified, with rapid tar evolution prior to the onset of swelling associated with permeability change. Further tar release and gas evolution is associated with a rapid swelling event, this event being substantially greater for the high vitrinite sample. The data has also quantified contraction at higher temperatures following swelling which is associated with the release of hydrogen containing gases. Evolved tars from the high vitrinite sample showed elevated H/C ratio indicating that vitrinite tars appear to be more aliphatic than those evolved from inertinite. A comparison of measured swelling with estimated volumetric flow rate of the volatiles has indicated that thermo-expansion of coal utilised up to 21% of the volatiles to drive bubble growth. This utilisation rate varied significantly across the plastic temperature range.